Paediatric injuries due to falls from windows and balconies: an 8-year prospective and retrospective review. Issue 5 (20th August 2020) - Rajagopal, Manasi; Kundra, Manu; Mabood, Neelam; Ali, Samina; Rankin, Tara; Dow, Nadia; Craig, William
Abstract: Background: Unintentional falls from windows and balconies pose a serious health risk to children. Limited Canadian data describing such falls currently exist. This study aimed to describe the frequency, demographic characteristics, injury patterns, and risk factors associated with paediatric falls from windows and balconies. Methods: This study employed both prospective data collection and retrospective medical record review. Prospectively, consenting families were enrolled from February 2015 to February 2017; retrospectively, charts from January 2009 to December 2014 were reviewed. Children 0 to 16 years of age, who presented to the Stollery Children's Hospital (Edmonton, Alberta) emergency department due to a fall from a window or balcony, were included. Results: A total of 102 children were included; thirty were enrolled prospectively and 72 retrospectively. Median age was 4.5 years (interquartile range 2.83 to 6.83) with 63.7% (65 of 102) males. About 87.2% (89 of 102) of falls were from windows and 12.8% (13 of 102) from balconies. The median estimated height of fall was 4.1 m (interquartile range 3.04 to 4.73). About 58.4% (59 of 101) had at least one major injury (i.e., concussion, fractured skull, internal injury, fractured limb, severe laceration), 36.6% had minor injuries only (i.e., abrasions, contusions, sprains), and 5.0% had no documented injuries. There were no fatalities. About 30.4% (31 of 102) were admitted, with 48.4% of these children (15 of 31) requiring surgery. Conclusion: Most falls from windows and balconies occurred in children under the age of 5 years and were associated with serious morbidity, high admission rates, and need for surgery. Child supervision as well as installation of key safety features in windows may help minimize paediatric fall-related injuries.